Temporal profile of care following mild traumatic brain injury: predictors of hospital admission, follow-up referral and six-month outcome. (6th December 2017) - Yue, John K.; Winkler, Ethan A.; Sharma, Sourabh; Vassar, Mary J.; Ratcliff, Jonathan J.; Korley, Frederick K.; Seabury, Seth A.; Ferguson, Adam R.; Lingsma, Hester F.; Deng, Hansen; Meeuws, Sacha; Adeoye, Opeolu M.; et al.
ABSTRACT: Objective : To investigate the clinical management and medical follow-up of patients with mild traumatic brain injury (mTBI) presenting to emergency departments (EDs). Methods : Overall, 168 adult patients with mTBI from the prospective, multicentre Transforming Research and Clinical Knowledge in TBI (TRACK-TBI) Pilot study with Glasgow Coma Scale (GCS) 13–15, no polytrauma and alive at six months were included. Predictors for hospital admission, three-month follow-up referral and six-month functional disability (Glasgow Outcome Scale-Extended (GOSE) ≤ 6) were analysed using multivariable regression. Results : Overall, 48% were admitted to hospital, 22% received three-month referral and 27% reported six-month functional disability. Intracranial pathology on ED head computed tomography (multivariable odds ratio (OR) = 81.08, 95% confidence interval (CI) [10.28–639.36]) and amnesia (>30-minutes: OR = 5.27 [1.75–15.87]; unknown duration: OR = 4.43 [1.26–15.62]) predicted hospital admission. Older age (per-year OR = 1.03 [1.01–1.05]) predicted three-month referral, while part-time/unemployment predicted lack of referral (OR = 0.17 [0.06–0.50]). GCS < 15 (OR = 2.46 [1.05–5.78]) and prior history of seizures (OR = 3.62 [1.21–10.89]) predicted six-month functional disability, while increased education (per-year OR = 0.86 [0.76–0.97]) was protective. Conclusions : Clinical factors modulate triage to admission, while demographic/socioeconomic elements modulate follow-up care acquisition; six-month functional disability associates with both clinical and demographic/socioeconomic variables. Improving triage to acute and outpatient care requires further investigation to optimize resource allocation and outcome after mTBI. ClinicalTrials.gov registration: NCT01565551